sIFITM1, sIFITM3, and sViperin antiviral proteins as inactivated CSFV vaccine adjuvants - Liu, Shasha; Zhou, Wenzhuo; Ye, Haobo; Qiu, Feng; Gu, Rongrong; Xu, Erying; Chen, Ji-Long (Frontiers in Veterinary Science, 2025)
Vaccine adjuvants are now widely utilized in vaccine formulations. The IFN-Stimulated Genes (ISGs) family, play crucial roles in immune regulation and exhibit broad-spectrum antiviral activity. However, limited studies have investigated the potential of ISGs as vaccine adjuvants. Here, three swine ISGs fusion proteins were induced and purified from Escherichia coli, including IFITM1, IFITM3 and Viperin (sIFITM1, sIFITM3, and sViperin). Furthermore, sIFITM1, sIFITM3, and sViperin inhibited the replication of pseudorabies virus (PRV) in swine (PK-15 and 3D4/21) and murine (NIH/3 T3 and C57/B6-L) cells. Importantly, these fusion proteins effectively enhanced the immunogenicity of inactivated classical swine fever virus (CSFV) vaccine and improved the immune response in vaccinated mice. Our evidence indicates that, compared with the CSFV vaccine group, the co-administration of sIFITM1, sIFITM3, and sViperin with CSFV vaccine significantly improved humoral immunity, increased T lymphocyte proliferation in the spleen, and elevated serum IgG antibody levels. In conclusion, this study successfully prepared sIFITM1, sIFITM3, and sViperin fusion proteins, confirming their ability to inhibit PRV replication and suggesting their potential as vaccine adjuvants.